Unlikely Environmentalists : Congress and Clean Water, 1945 - 1972 - Milazzo, Paul Charles (Book collections on Project MUSE., 2006)
"Environmental activism has most often been credited to grassroots protesters, but much early progress in environmental protection originated in the halls of congress. As Paul Milazzo shows, a coterie of unlikely environmentalists placed water quality issues on the national agenda as early as the 1950s and continued to shape governmental policy through the early 1970s, both outpacing public concern and predating the environmental movement." "Milazzo examines a two-decade crusade to clean up the nation's water supply led by development boosters, pork barrel politicians, and the Army Corps of Engineers, all of whom framed threats to the water supply as an economic rather than environmental problem and saw pollution as an inhibitor of regional growth. Demonstrating that legislative branch acted more assertively than the executive, the book weaves the history of the federal water pollution control program into a broader narrative of political and institutional development, covering all major clean water legislation as well as many other landmark environmental laws."--Jacket.